Os desafios do Programa Nacional de Alimentação Escolar (PNAE) na Escola Professor Rildo Valadares, na Comunidade Quilombola Oxalá de Jacunday – Moju/PA - VALADARES, Leonora do Carmo (2022)
This article is the result of research carried out at the Rildo Valadares school, in the quilombola community Oxalá de Jacunday, municipality of Moju / PA on the challenges of the National School Feeding Program (PNAE) within the school. The field study was carried out from September 2019 to May 2020. Methodologically, a bibliographic review and a brief field research were carried out, which unfortunately was interrupted due to the COVID-19 pandemic, but with all the necessary care I was able to return and conclude. The work aims to analyze the challenges faced by the school studied with regard to access to PNAE and understand how the program contributes to the teaching-learning process of students. As one of the results, it is possible to affirm that the enormous advances that have occurred in the PNAE would hardly be possible if there were not a political, institutional and technical scenario that would encourage a broad and integrative approach to food policies and programs.